Government of Sri Lanka revises Food for Assets program to be more nutrition-sensitive based on guidance from A4NH and the World Food Program - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Type of social protection program, coupled with behavior change communication on agriculture, nutrition and well-being, designed to build resilience of smallholder farmers and promote positive health and nutrition behavior changes.